Coherent fusion of water array and protonated amine in a metal-sulfate-based coordination polymer for proton conduction - Manna, Biplab; Anothumakkool, Bihag; Desai, Aamod V.; Samanta, Partha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2015)
A new function of metal-sulfate-based co-ordination polymer (CP) for proton,conduction Was investigated through rational integration of a continuous water array and protonated amine in the coordination space of the CP. The H-bonded arrays of watet molecules along with nitrogen-rich aromatic cation (protonated melamine) facilitate proton conduction in the compound under humid conditions. Although several reports of metal-oxalate/phosphate-based CPs showing proton conduction are known, this is the first designed synthesis of a metal sulfate-based CP bearing-Water arrays functioning as a solid-state proton conductor:

Ultrahydrophobic fluorous metal-organic framework derived recyclable composite as apromising platform to tackle marine oil spills - Mukherjee, Soumya; Kansara, Ankit M.; Saha, Debasis; Gonnade, Rajesh; Mullangi, Dinesh; Manna, Biplab; Desai, Aamod V.; Thorat, Shridhar H.; Singh, Puyam S.; Mukherjee, Arnab; Ghosh, Sujit K. (Chemistry-A European Journal, 2016)
Derived from a strategically chosen hexafluorinated dicarboxylate linker aimed at the designed synthesis of a superhydrophobic metal-organic framework (MOF), the fluorine-rich nanospace of a water-stable MOF (UHMOF-100) exhibits excellent water-repellent features. It registered the highest water contact angle (approximate to 176 degrees) in the MOF domain, marking the first example of an ultrahydrophobic MOF. Various experimental and theoretical studies reinforce its distinc-tive water-repellent characteristics, and the conjugation of superoleophilicity and unparalleled hydrophobicity of a MOF material has been coherently exploited to achieve real-time oil/water separation in recyclable membrane form, with significant absorption capacity performance. This is also the first report of an oil/water separating fluorinated ultrahydrophobic MOF-based membrane material, with potential promise for tackling marine oil spillages.

Ultrahigh ionic conduction in water-stable close-packed metal-carbonate frameworks - Manna, Biplab; Desai, Aamod V.; Illathvalappil, Rajith; Gupta, Kriti; Sen, Arunabha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2017)
Utilization of the robust metal-carbonate backbone in a series of water-stable, anionic frameworks has been harnessed for the function of highly efficient solid-state ion conduction. The compact organization of hydrophilic guest ions facilitates water-assisted ion-conduction in all the compounds. The dense packing of the compounds imparts high ion-conducting ability and minimizes the possibility of fuel crossover, making this approach promising for design and development of compounds as potential components of energy devices. This work presents the first report of evaluating ion-conduction in a purely metal-carbonate framework, which exhibits high ion-conductivity on the order of 10(-2) S cm(-1) along with very low activation energy, which is comparable to highly conducting well-known crystalline coordination polymers or commercialized organic polymers like Nafion.